2005
DOI: 10.1111/j.1365-313x.2005.02357.x
|View full text |Cite
|
Sign up to set email alerts
|

shk1‐D, a dwarf Arabidopsis mutant caused by activation of the CYP72C1 gene, has altered brassinosteroid levels

Abstract: SummaryBrassinosteroids (BRs) are plant steroidal hormones that regulate plant growth and development. An Arabidopsis dwarf mutant, shrink1-D (shk1-D), was isolated and the phenotype was shown to be caused by activation of the CYP72C1 gene. CYP72C1 is a member of the cytochrome P 450 monooxygenase gene family similar to BAS1/CYP734A1 that regulates BR inactivation. shk1-D has short hypocotyls in both light and dark, and short petioles and siliques. The seeds are also shortened along the longitudinal axis indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
97
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 40 publications
(117 reference statements)
9
97
0
Order By: Relevance
“…664 An Arabidopsis dwarf mutant overexpressing the P450 665 monooxygenase gene CYP72C1 (shk1-D) showed a 666 reduction in endogenous BR levels and produced smaller 667 seeds than the wild type, probably due to an effect on cell 668 elongation (Takahashi et al 2005). A similar small seed 669 phenotype was reported in the DWARF5 (DWF5) loss-of-670 function mutant.…”
mentioning
confidence: 83%
“…664 An Arabidopsis dwarf mutant overexpressing the P450 665 monooxygenase gene CYP72C1 (shk1-D) showed a 666 reduction in endogenous BR levels and produced smaller 667 seeds than the wild type, probably due to an effect on cell 668 elongation (Takahashi et al 2005). A similar small seed 669 phenotype was reported in the DWARF5 (DWF5) loss-of-670 function mutant.…”
mentioning
confidence: 83%
“…Recently, it has been reported that the expression of Arabidopsis CYP734A1/CYP72B1 and CYP72C1, both encoding BR-catabolizing P450s, are light repressed (Turk et al, 2003;Takahashi et al, 2005), indicating the possibility of coordinated regulation of these genes and light-inducible CPD and CYP85A2 that encode biosynthetic enzymes. Light-activated CYP85A2 and lightrepressed CYP734A1/CYP72B1 and CYP72C1 expression seem consistent with the observed appearance of BL in young seedlings at midday.…”
Section: Discussionmentioning
confidence: 99%
“…Biosynthesis and inactivation are coordinated via BR-dependent transcriptional control of the genes involved in both processes. All BR-biosynthetic P450 genes of Arabidopsis are under negative feedback regulation by active BRs (Bancos et al, 2002;Tanaka et al, 2005), whereas of those encoding inactivating enzymes only BAS1 was found BR inducible (Choe et al, 2001;Takahashi et al, 2005). Feedback regulation of CPD is abolished in the BR-insensitive bin2 and brassinosteroid insensitive 1-2 (bri1-2)/cbb2 mutants (Li et al, 2001;Bancos et al, 2002), indicating a key role of BR signaling in the hormonal self-regulation of BR biosynthesis and perhaps also inactivation.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The CYP72A subfamily is highly expanded across higher plants, and often the genes are arranged in tandem arrays as seen with the nine CYP72As in Arabidopsis, which are clustered on chromosome 3. Arabidopsis contains a single CYP72C, which, based on mutant analysis, is involved in deactivation of brassinolides, although the precise biochemical function and substrate is not known [62,73,74]. CYP72C appear to be Brassicaceae-specific, arguing that involvement in brassinolide inactivation is not the original in planta function of CYP72s.…”
Section: Recruitment Of P450s For Triterpenoid Biosynthesismentioning
confidence: 99%